2015
DOI: 10.1002/adsc.201500701
|View full text |Cite
|
Sign up to set email alerts
|

Iron(III)/Iodine‐Catalyzed C(sp2)H Activation of α,β‐Unsaturated Aldehydes/Ketones with Amidines: Synthesis of 1,2,4,5‐Tetrasubstituted Imidazoles

Abstract: An efficient methodology to access a library of 1,2,4,5‐tetrasubstituted imidazoles from a broad range of amidines and α,β‐unsaturated aldehydes/ketones via a C(sp2)H amination has been developed. This method represents a new and simple way to prepare highly substituted imidazoles from easily available starting materials, inexpensive catalysts, and with good functional group tolerance in good to excellent yields.magnified image

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 84 publications
0
19
0
Order By: Relevance
“…also independently developed an excellent methodology for the synthesis of imidazole derivatives from the α , β ‐unsaturated aldehydes/ketones (Scheme 36). [39] During the optimization of the reaction conditions, they found that the best result was obtained by carrying out the reaction in presence of FeCl 3 .6H 2 O (10 mol%), 1,10‐phenanthroline (10 mol%) and I 2 (2.5 mol%) in 1,2‐dichlorobenzene at 110 °C under aerobic conditions. Although, the reaction also proceeded in absence of I 2 however the presence of I 2 increased the yield dramatically.…”
Section: Synthesis Of Heterocycles Via Oxidative Couplingmentioning
confidence: 99%
“…also independently developed an excellent methodology for the synthesis of imidazole derivatives from the α , β ‐unsaturated aldehydes/ketones (Scheme 36). [39] During the optimization of the reaction conditions, they found that the best result was obtained by carrying out the reaction in presence of FeCl 3 .6H 2 O (10 mol%), 1,10‐phenanthroline (10 mol%) and I 2 (2.5 mol%) in 1,2‐dichlorobenzene at 110 °C under aerobic conditions. Although, the reaction also proceeded in absence of I 2 however the presence of I 2 increased the yield dramatically.…”
Section: Synthesis Of Heterocycles Via Oxidative Couplingmentioning
confidence: 99%
“…In 2015, they developed a facile iron(III)‐catalyzed C−H amination to access highly substituted imidazoles with good to excellent yields using α , β ‐unsaturated aldehydes/ketones and amidines as starting materials (Scheme 15). [38a] The additive, I 2 , played a dual role in this transformation involving the function II and III . On the one hand, I 2 could prompt the transformation of an intermediate I52 into I53 with the release of HI, which followed by an intramolecular nucleophilic cyclization to form an intermediate I54 .…”
Section: Oxidizing Component‐induced Reactionsmentioning
confidence: 99%
“…[187] Still in 2015, Chen and coworkers described efficient regioselective syntheses of 5-aroyl-1,2,4triaryl-1H-imidazoles 56 via iron(III)/iodinecatalyzed Csp 2 -H activation of a,b-unsaturated ketones/aldehydes with amidines. [190] . Compounds 56 were generally obtained in good to excellent yields by treatment of 1 equiv of a,b-unsaturated ketones 152 with 1.2 equiv of amidines 151 in 1,2dichlorobenzene (1,2-DCB) in the presence of 10 mol% FeCl3×××6H2O, 2.5 mol% I2 and 10 mol% 1,10phenanthroline (1,10-phen) (Scheme 83).…”
Section: Scheme 81 Fecl3/i2-catalyzed Aerobic Oxidative Coupling Reaction Of Amidines 151 With Chalcones 152mentioning
confidence: 99%